Таксономические заметки о некоторых прямокрылых (Orthoptera) Кавказа - Столяров, M.В. (Вестник зоологии, 1984)
Taxonomic Notes on Some Orthoptera of the Caucasus. Stolyaroy M. V.— Vestn.
zool., 1984, No. 3. New synonymies and new combinations are established: Tettigonia
caudata (Charpentier, 1845) =T. caudata armeniaca Tarbinsky, 1940, syn.n.;
Phylodrymadusa miramae (Uvarov, 1929) =Ph. armeniaca Ramme, 1939, syn.n.;
Psorodonotus caucasicus anatolicus Karabag, statn; Psorodonotus specularis (Fischer-Waldheim, 1839) =P. specularis inermis Ramme, 1951, syn.n.; Nocarodes
serricollis santi-davidi (Shugurov, 1912) . transcaucasicus Ramme, 1951, sun.n.;
Paranocaracris rubripes tristis (Ramme, 1951), comb.n. Geographic distribution of the
above taxa is defined more accurately.